Longitudinal command stability augmentation system design for unstable aircraft using flying and handling qualities specifications - Mansor, S. (Institute of Electrical and Electronics Engineers Inc., 2016)
This paper demonstrates a practical approach in designing a longitudinal command stability augmentation system for unstable combat aircraft. The unaugmented aircraft is originally unstable configuration in order to gain fast response for agility. The flight control system was designed in compliance with MIL-F-8785C and Gibson Criterion for the corresponding flight case. The design case study is based on pitch rate command control system using I controller. The design evaluation is based on time response analysis of simulated results using Matlab and Simulink. The pole-placement method was used to determine the augmented feedback gain. Second order actuator dynamics model was introduced to see its effect on overall design. This design case study offers a better understanding, an easier and practical approach implementation based on aircraft longitudinal pitch rate command.